Rehabilitation applications and progress in managing pulmonary hypertension - Liu, Yuyan; Guo, Xiao; Liu, Panpan; Jia, Shuying; Wang, Fang; Li, Fei; Yuan, Ping; Wang, Xuejing (Frontiers in Medicine, 2025)
Pulmonary hypertension (PH) is a significant global health challenge that profoundly impacts exercise tolerance and quality of life for affected individuals. While advancements in pharmacological therapies have improved symptom management, exercise capacity, and overall well-being, there is a growing recognition of rehabilitation therapy as a promising non-pharmacological approach. Rehabilitation therapy aims to restore or enhance physical, psychological, and social functioning in individuals compromised by disease, injury, or congenital conditions through an integrated approach encompassing medical, social, and educational interventions. In the context of PH, rehabilitation therapy encompasses diverse modalities, including exercise training, inspiratory muscle training, neuromuscular electrical stimulation, and psychological support. These interventions target key symptoms such as exercise intolerance and dyspnea, with the goal of improving patient outcomes and fostering a return to independent and meaningful living. Emerging evidence demonstrates that rehabilitation therapy is both safe and effective in enhancing cardiopulmonary function, muscle strength, and exercise capacity. Furthermore, it has been shown to alleviate anxiety and depression, improve quality of life, and facilitate reintegration into familial and social roles. This review provides a comprehensive overview of the clinical features, prevalence, and current treatment landscape of PH, with a particular focus on the role and advancements in rehabilitation therapy. We discuss the therapeutic potential of rehabilitation therapy in addressing the multifaceted challenges of PH and explore future directions and innovative approaches in this evolving field. By highlighting the clinical utility and research progress of rehabilitation therapy, this review aims to offer new insights and perspectives for optimizing the management of PH and improving patient outcomes.